Passive Air Samplers As a Tool for Assessing Long-Term Trends in Atmospheric Concentrations of Semivolatile Organic Compounds - Kalina, Jiří; Scheringer, Martin; Borůvková, Jana; Kukučka, Petr; Přibylová, Petra; Bohlin-Nizzetto, Pernilla; Klánová, Jana (Environmental science & technology, 2017)
Many attempts have been made to quantify the relationship between the amount of persistent organic pollutants sequestered by passive air sampling devices and their actual concentrations in ambient air. However, this information may not be necessary for some applications. In this study, two sets of 30 ten-year-long time series of simultaneous passive and high-volume active air sampling carried out at the Košetice observatory in the Czech Republic were used for a comparison of temporal trends. Fifteen polyaromatic hydrocarbons, seven polychlorinated biphenyls and eight organochlorine pesticides were investigated. In most cases, a good agreement was observed between the trends derived from passive and active monitoring with the exception of several compounds obviously affected by sampling artifacts. Two sampling artifacts were observed: breakthrough of high-volume sampler filters for penta- and hexachlorobenzene and semiquantitative values for PAHs with a high molecular weight. It has been suggested before that annually aggregated results of passive air monitoring may be used directly for the assessment of the long-term behavior of these compounds. The extensive set of long-term data used in this study allowed us to confirm this finding and to demonstrate that it is also possible to derive temporal trends and the compounds' half-lives in air from the passive-sampling time series.
Keywords: monitorování životního prostředí; Czech Republic; látky znečišťující vzduch; Hydrocarbons, Chlorinated; polycyklické aromatické uhlovodíky; chlorované uhlovodíky; Česká republika; polychlorované bifenyly; Polycyclic Aromatic Hydrocarbons; Air Pollutants; Environmental Monitoring; Polychlorinated Biphenyls